Reconstruction of Soil Particle Composition During Freeze-Thaw Cycling： A Review - ZHANG, Ze; MA, Wei; FENG, Wenjie; XIAO, Donghui; HOU, Xin (Pedosphere, 2016)
Studies conducted over several decades have shown that the freeze-thaw cycles are a process of energy input and output in soil, which help drive the formation of soil structure, through water expansion by crystallization and the movement of water and salts by thermal gradients. However, most of these studies are published in Russian or Chinese and are less accessible to international researchers. This review brought together a wide range of studies on the effects of freezing and thawing on soil structure. The following findings are summarized： i） soil structure after freeze-thaw cycles changes considerably and the changes are due to the mechanical fragmentation of soil coarse mineral particles and the aggregation of soil fine particles; ii） the particle size of soil becomes homogeneous and the variation in soil structure weakens as the number of freeze-thaw cycles increases; iii） in the freezing process of soil, an important principle in the variation of soil particle bonding is presented as： condensation →aggregation→ crystallization; iv） the freeze-thaw cycling process has a strong effect on soil structure by changing the granulometric composition of mineral particles and structures within the soil. The freeze-thaw cycling process strengthens particle bonding, which causes an overall increase in aggregate stability of soil, showing a process from destruction to reconstruction.